2021
DOI: 10.1002/cjoc.202000508
|View full text |Cite
|
Sign up to set email alerts
|

Feng Ligand: Privileged Chiral Ligand in Asymmetric Catalysis

Abstract: Feng ligand | N,N'-Dioxide | O ligands | Asymmetric catalysis | Lewis acids Catalysts and ligands possessing the great ability to tolerate over a wide range of mechanistically unrelated reactions are remarked as "privileged", which are rather scarce but extremely meaningful in asymmetric catalysis. Feng and co-workers have developed a library of conformationally flexible, C 2-symmetric N,N'-dioxide amide compounds with original design and featured structure (named as Feng ligand now). They were initially repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(25 citation statements)
references
References 118 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…The latter two were hard to separate, and the thermodynamically unstable ( Z )- C1 was isolated as the major product in most cases. In the reaction with chiral Feng N , N′ -dioxide L 3 -Tq t Bu as the ligand and Co­(OTf) 2 as the metal precursor, ( Z )- C1 was isolated in 66% yield with 97% ee, and the combined yield of ( E )- C1 and D1 was around 20% with 90:10 ratio (entry 1). The α/γ-regioselectivity was high and the γ-insertion products dominated.…”
Section: Resultsmentioning
confidence: 99%
“…The latter two were hard to separate, and the thermodynamically unstable ( Z )- C1 was isolated as the major product in most cases. In the reaction with chiral Feng N , N′ -dioxide L 3 -Tq t Bu as the ligand and Co­(OTf) 2 as the metal precursor, ( Z )- C1 was isolated in 66% yield with 97% ee, and the combined yield of ( E )- C1 and D1 was around 20% with 90:10 ratio (entry 1). The α/γ-regioselectivity was high and the γ-insertion products dominated.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the frequent occurrence of the spirocyclobutyl oxindole skeleton in bioactive molecules, 12 h – j ,15 it is highly desirable to develop reliable access to spirocyclobutyl oxindole derivatives. 16 In continuation with our interest in chiral N , N ′-dioxide/metal Lewis acid catalysis 17 and inspired by elegant studies 5,13,14 on the N -allenamide chemistry, herein, we demonstrated that catalysts could promote the direct asymmetric [2+2] cycloaddition of ( E )-alkenyloxindoles with N -allenamides for straightforward access to optically active spirocyclobutyl oxindole derivatives ( Scheme 1b ). Moreover, further diversified transformation 18 of the internal C C bond-involved product catalyzed by a copper salt enabled the one-pot synthesis of tetradropyranoindole derivatives, which seem to be the formal [4+2] cycloaddition adducts of the terminal C C bond of N -allenamides.…”
Section: Introductionmentioning
confidence: 74%
“…Homogeneous asymmetric catalyst has made significant progress in the last decade, due to its facile interaction between the catalyst and the reactant which results in high activity and selectivity. The main pitfall is separation of the catalyst from the products, which often leads to loss of the catalyst [1,2] . Another drawback is leaching of the metal from the homogeneous catalysts into the products.…”
Section: Introductionmentioning
confidence: 99%